Integrating of Digital Literacy and Achievement Motives for Learning Activities in Universities After the Covid-19 Pandemic - Harapan, Edi; Suherman; Utama, Cholidah; Wang, Yuanyuan; Zou, Guijiao (Journal International Inspire Education Technology, 2023)
The research aims to analyze and describe the integration of digital literacy and achievement motives in post-covid-19 post-pandemic tertiary learning activities using a quantitative method with a correlational approach. The research location was at the Sharia Faculty of UIN Raden Fattah Palembang, from a population of 256 students. Data was collected using observation, documentation, and questionnaires. The results of the study found that the integration of digital literacy and achievement motives partially and simultaneously had a low effect on post-covid-19 learning activities. It was concluded that learning activities at the Sharia Faculty of UIN Raden Fatah Palembang had combined digital literacy with achievement motives in learning activities that had not been fully successful. It is recommended that total changes be made to learning activities by maximizing digital literacy integration and increasing achievement motives for lecturers and students. Learning activities will not run effectively if digital literacy interactions with achievement motives from lecturers and students are not carried out optimally.